Pengaruh Atmosphere, Word Of Mouth, Dan Kualitas Pelayanan Terhadap Loyalitas Melalui Kepuasan Pengunjung: Studi Empiris Pada Wisata Bukit Gandrung Kediri. - Nurlaily Adi Putrie; Nurhidayah Nurhidayah; Kartika Rose Rachmadi (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract The tourism sector continues to grow and contributes significantly to the Indonesian economy. Bukit Gandrung Tourism in Kediri is one of the destinations experiencing rapid development. Increasing competition among tourist attractions requires effective strategies to build visitor loyalty through satisfaction. This study aims to analyze the effect of atmosphere, word of mouth, and service quality on visitor loyalty through visitor satisfaction at Bukit Gandrung Kediri. This research uses a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to 120 visitors who met the research criteria. Data analysis used Structural Equation Modeling–Partial Least Square (SEM-PLS) with SmartPLS 4.0. The results show that atmosphere, word of mouth, and service quality significantly influence visitor satisfaction. These variables also significantly affect visitor loyalty. In addition, visitor satisfaction significantly influences visitor loyalty and mediates the relationship between atmosphere, word of mouth, service quality, and visitor loyalty. These findings provide insights for tourism managers in improving visitor loyalty by enhancing visitor satisfaction. Keywords: Atmosphere, Word of Mouth, Service Quality, Visitor Loyalty,Visitor Satisfaction.